2021
DOI: 10.1177/14614448211024546
|View full text |Cite
|
Sign up to set email alerts
|

‘Welcome to #GabFam’: Far-right virtual community on Gab

Abstract: With large social media platforms coming under increasing pressure to deplatform far-right users, the Alternative Technology movement (Alt-Tech) emerged as a new digital support infrastructure for the far right. We conduct a qualitative analysis of the prominent Alt-Tech platform Gab, a social networking service primarily modelled on Twitter, to assess the far-right virtual community on the platform. We find Gab’s technological affordances – including its lack of content moderation, culture of anonymity, micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 58 publications
1
36
0
1
Order By: Relevance
“…They dont wanna deal with this level of autism Ultimately, Gab creates an "echo chamber" that shapes users, including autistic users. Gab is specifically designed for people to express extreme views in a forum where it will not be challenged (Jasser et al, 2021). Additionally, Gab discourse has been found to be driven by "super participants" who work to ensure dissenting / divergent views are discouraged (Zhou et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…They dont wanna deal with this level of autism Ultimately, Gab creates an "echo chamber" that shapes users, including autistic users. Gab is specifically designed for people to express extreme views in a forum where it will not be challenged (Jasser et al, 2021). Additionally, Gab discourse has been found to be driven by "super participants" who work to ensure dissenting / divergent views are discouraged (Zhou et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…It proclaims itself to be "a social network that champions free speech, individual liberty and the free flow of information online" (Gab.com, 2021). It has been widely criticized by hate watch groups, journalists, and researchers as being a harbor for extremist and hate-based discourse (Donovan et al, 2018;Jasser et al, 2021). Jasser and colleagues (Jasser et al, 2021) conducted an analysis of Gab posts and found a high frequency of hate speech among users posting public messages, most commonly communicating anti-left, anti-Semitic, misogynistic, racist, and xenophobic sentiments.…”
Section: Description Of Data Source: Gabmentioning
confidence: 99%
See 3 more Smart Citations